Scoring System Otomatis Pada Lomba Menembak Dengan Target Silhouette Hewan Menggunakan Metode K-Nearest Neighbor (K-NN) - Syahriel Diovanni Yolanda; Rizal Maulana; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Shooting sport is a one type of sport. Sports shooting is a sport of agility because this sport can increase the level of focus and capture a person. Through sports shooting someone trained and required to be able to concentrate, able to control themselves and dare to make decisions quickly and accurately. Shooting is a self-control exercise. In determining one's expertise in firing, an accurate scoring system is required. In a generalized scoring system, manual shooting requires an observer / judge to assess the firing result. The scoring system manually takes more time in delivering the information to the audience. In this study we will create an Automated Scoring System On Shooting Contest With Animal Silhouette Target Using K-Nearest Neighbor Method to determine which type of Silhouette is shot and add score on the system monitor. The K-Nearest Neighbor method is used in the classification process of the shooting Silhouette type to give effect to the score in the race. In this system uses some components of vibration sensor SW-420, Load Cell, Limit Switch, Switch, Module HX711, and Arduino Mega 2560 as much as 2 processors. Based on test result on this system, the accuracy level of sensor data is 96,42% and accurate to K-Nearest Neighbor classification is 100%.